ANALISIS KINERJA SIMPANG BUNGA SETANGKAI DI KECAMATAN PAYAKUMBUH KABUPATEN LIMA PULUH KOTA - Emril, Nofriyan; Yermadona, Helga; Endri, Endri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
A road intersection can be described as a common area that joins or crosses two or more roads. Lima Puluh Kota Regency has 8 intersections which have 3 intersection legs. There is 1 intersection at intersection 3 without a signal with type 322 intersection, namely the Bunga Setangkai intersection, this intersection has side barriers such as shops and one of the legs of the intersection, namely Tan Malaka 1, is a school. To assess the level of service at intersections, capacity, degree of saturation, delays and queuing opportunities need to be analyzed using the Indonesian Road Capacity Guidelines (PKJI, 2023). From the results of the analysis, the value of the degree of saturation is 0.88, the minimum chance of queuing is 32% and the maximum is 62% and the average delay is 15.05 sec/pcu so that the level of service at the Bunga Setangkai intersection is C. The researcher recommends making changes to the type of intersection control become a roundabout, and reduce side obstacles at intersections by implementing no parking at intersections, in order to improve performance at the Bunga Setangkai intersection. Analysis of the condition of the proposed intersection performance results in the following intersection performance. The first proposal with existing conditions is to change the type of control at the intersection to a roundabout. By carrying out proposal 1, it is possible to increase the capacity of the intersection by widening the road at the foot of the intersection. From the analysis of the calculation of the saturation level of the intersection which has exceeded the maximum value set, namely 0.88, it shows a decrease in performance at the intersection. According to the geometric planning module for at-grade intersections, the width of one The standard lane is 3.5 meters. Thus, if a vehicle with a maximum width of 2.5 meters passes, there is still 0.5 meter of empty space to the right and left of the vehicle. The second proposal is to add signs at intersections, by changing the side barriers to 0.95 by implementing no parking signs and priority signs at the Bunga Setangkai intersection so that road drivers do not park their vehicles on the shoulder of the road until they hit the road and avoid conflicts between vehicles.Keywords: Unsignalized intersection, delays